Penggunaan Media Pembelajaran Audiovisual PowerPoint Untuk Mengenalkan Nama Hewan dalam Bahasa Inggris - Rosalinda, Vica Retno; Rusdiani, Nurtina Irsad (Insititut Agama Islam Negeri (IAIN) Curup, 2024)
Learning media is one of the learning tools that teachers need to be able to select, use and apply media that represents areas that cannot be compromised during the process. Audiovisual media has the potential to make learning more interesting, making children enthusiastic about learning. The aim of this research is to determine the use of PPT audiovisual learning media to introduce animal names in English at POCENTER. The qualitative research method is research carried out through observation. The post-positivist lens is used for empirical analysis under well-defined experimental conditions. The results of this research are that Pocenter has started using PowerPoint for teaching. Teaching media is one of the tools used in the learning process which has important lessons to be learned from the teaching method. With this media, when the learning objectives have been achieved, the transmission of knowledge and education can run smoothly. Therefore, educators need to understand each media that will be used to carry out teaching and learning activities effectively.